Effect of Obstructive Sleep Apnea on Sleep Pattern and Blood Glucose Level in Type 2 Diabetes Patients - Sah, Santosh Kumar; Rajput, Jay Prakash Singh; Rochlani, Dimpal; Inamdar, R. S. (Nepalese Medical Journal, 2022)
Introduction: Our physical, mental, and emotional well-being require normal sleep. Disturbances in sleep quality and quantity can result in metabolic disorders. Sleep fragmentation increases sympathetic activity which leads to decreased insulin sensitivity. Obstructive sleep apnea causes sleep fragmentation. That is why this study attempt is made to find the effect of obstructive sleep apnea on sleep pattern and blood glucose level in type 2 diabetes patients. Materials and Method: Depending on the severity of the Apnea-Hypopnea Index (AHI) recorded by polysomnography, each, volunteer were divided into two groups, a) AHI>10 groups, and b) AHI≤10 groups. Then the comparison of all the parameters between AHI>10 and AHI≤10 groups of diabetic participants was done. Results: In participants of AHI≤ 10 groups, Sleep efficiency%, Mean TBI SPo2%, sleep Stage III%, and REM% are significantly higher as compared to AHI>10 groups. In participants of the AHI>10 groups, sleep Stage I%, the score of ESS, and fasting blood glucose level are significantly higher as compared to AHI≤ 10 groups. Conclusions: Increasing AHI is associated with reduced sleep efficiency; a sleep stage of N3%, and a REM sleep phase, which lead to an increase in fasting blood glucose levels in the diabetic group.